A SOCIO-PRAGMATIC ANALYSIS OF ABUSIVE UTTERANCES IN COMEDY MOVIE MANUSCRIPT - Chielmiaty, Aldise Yofa (2010)
This research deals with abusive utterances in comedy movie manuscript. The aims of this research are to identify the form, to describe the implicature and to describe the politeness patterns of the abusive utterances in comedy movie manuscript. The type of this research is descriptive qualitative. The data source of this research is comedy movie manuscript, The Pacifier. The writer takes 37 data of abusive utterances in The Pacifier movie. The method of collecting data is documentation and the steps are reading, selecting and collecting, and coding the data. The method of analyzing data is descriptive technique. The analysis of the form is based on linguistic form, especially the types of sentences. While the analysis of implicature is by referring to the context of pragmatics. Then, the analysis of the politeness patterns is by using politeness principle. This study shows the variety of the form, implicature and politeness pattern of abusive utterances used in comedy movie manuscript. The variants of form of sentences are: (1) Declarative, (2) Interrogative, (3) Imperative and (4) Exclamatory. The implicature of the study covers implied meaning of conventional implicature and conversational implicature whose types are name-calling, denial, trivializing, accusing and blaming, withholding, discounting, judging and criticizing, undermining, ordering, and blocking and diverting. The politeness patterns are bald on record, positive politeness, and off record